Measurement of Liquid Droplet Evaporation Rate under the Conditions of Intense Heating; Applied Mechanics and Materials; Vol. 698 : Electrical Engineering, Energy, Mechanical Engineering – EEM 2014 - Orlova E. G. Evgeniya Georgievna (2015, 2015)
Title screen